SELF-DIFFUSION OF BCC INTERSTITIAL ALLOY FeSi - Quang Hoc, Nguyen; Duy Thanh, Pham; Dai Phuong, Duong (HNUE Journal of Science: Journal of Natural Sciences, 2025)
In this work, we present analytical formulations for self-diffusion parameters, namely the activation energy, pre-exponential factor, and self-diffusion coefficient as functions of temperature, pressure, interstitial atom concentration, and strain in a BCC interstitial binary alloy, derived using the statistical moment method (SMM). These theoretical models are utilized to perform numerical simulations for the FeSi alloy. The computed SMM values for FeSi are compared with those obtained for pure Fe. The SMM results for Fe show strong consistency with existing experimental measurements and alternative computational data. The additional SMM findings are novel and offer predictions that can guide future experimental investigations.